A method for producing a beta titanium alloy wire
Patent Information
- Application Number
- CN202611342441.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-01
- Publication Date
- 2026-10-30
AI Technical Summary
首先,国内加工β相钛合金丝材传统上多采用热拉拔或固定模拉拔结合中间单一退火加碱爆酸洗工艺,拉拔后丝材表面质量较差,且强塑性匹配较差难以满足高端眼镜框架生产用丝材的要求
本发明提供的β钛合金丝材的制备方法,采用变形量梯度减小的方式,以大变形量配合低温热处理形成粗冷挤压变形,实现快速减径,细化晶粒,在低温短时中间热处理,在促进合金发生再结晶的同时,避免β晶粒快速长大,中间冷挤压变形以采用中等减径变形量配合中温的中间热处理,为原子扩散和晶界迁移提供足够的热激活能,使晶粒发生再结晶,精冷挤压变形以小减径变形量的方式避免过大的变形量会导致严重加工硬化,通过β热处理为原子扩散和晶界迁移提供了充足的热激活能,能确保材料发生充分的静态再结晶,消除加工硬化,使组织恢复到低缺陷、高塑性的状态,挤压成型变形量显著大于传统的固定模拉拔。综上,本发明以多道次、梯度的“形变”与“相变”协同,制备的钛合金丝材弥补的纯钛作为眼镜架时弹性不足的缺陷,并且该丝材便于成型,能弯制或形成复杂的形状,避免了后续加工成型过程中被折裂的风险,使丝材在满足YS/T 1077-2015标准的同时,改善了钛合金丝材强塑性匹配以及低弹性模量,避免了后续加工成型过程中被折裂的风险。
Smart Images

Figure CN122999729A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of titanium alloy wire preparation technology, specifically relating to a method for preparing β titanium alloy wire. Background Technology
[0002] Titanium alloys, due to their outstanding advantages such as high specific strength, excellent corrosion resistance, and good biocompatibility, have become key structural materials in aerospace, biomedicine, and high-end consumer products. Among the many titanium alloy systems, β-type titanium alloys have received widespread attention in recent years due to their excellent cold workability, good heat treatment strengthening effect, and low elastic modulus. TB13 titanium alloy (nominal composition Ti-22V-4Al) is a medium-strength metastable β-type titanium alloy, known for its excellent cold formability and significant age-hardening effect. This alloy has extremely excellent cold workability in the solution state, allowing for convenient cold rolling, cold drawing, and cold bending operations, which lays a good technological foundation for the preparation of high-performance wire products. As the consumer market continues to pursue lightweight and comfortable eyewear products, requirements are being placed on the dimensional accuracy, surface quality, and mechanical properties (especially yield strength ratio and elastic modulus) of TB13 titanium alloy wire.
[0003] Although China has made some progress in the preparation of TB13 titanium alloy wire, there are still some problems that need to be solved. First, the traditional processing of β-phase titanium alloy wire in China mostly adopts hot drawing or fixed die drawing combined with intermediate single annealing and alkaline pickling process. The surface quality of the wire after drawing is poor, and the strength-plasticity matching is poor, which makes it difficult to meet the requirements of wire for the production of high-end eyeglass frames. Chinese patent CN122099098A discloses a method for preparing titanium alloy wire by drawing and the titanium alloy wire itself. The method involves performing multi-stage, multi-pass cold drawing on titanium alloy coils after peeling and polishing. When the cumulative deformation of each stage of multi-pass cold drawing reaches a preset value, online annealing is performed according to the specifications of the wire at the current stage, using different annealing temperatures and holding times. Then, the next stage of multi-pass cold drawing is performed. The titanium alloy wire obtained by multi-stage, multi-pass cold drawing on TB13 titanium alloy coils has a tensile strength ≥720MPa and a yield strength ≥670MPa, but its plasticity is relatively low, only ≤15%, indicating an unsatisfactory match between strength and plasticity. Chinese patent CN116532510A discloses a method for improving the mechanical properties of TB13 titanium alloy wire for eyeglass frames. The method uses rotary forging and roll drawing to cold reduce the diameter of TB13 titanium alloy wire and cold draw it, thereby improving the mechanical properties of the titanium alloy wire. However, the yield strength of the TB13 wire obtained by this method is ≤650MPa, which is lower than the mechanical property requirements in the YS / T 1077-2015 standard. Summary of the Invention
[0004] The purpose of this invention is to provide a method for preparing β-titanium alloy wire. The β-titanium alloy wire is prepared by cold extrusion molding. The cold extrusion deformation adopts a stepwise decreasing deformation method, using multiple passes and gradients to synergistically achieve deformation and phase transformation. The rough cold extrusion deformation uses a large deformation amount combined with low-temperature heat treatment to achieve rapid diameter reduction, refine grains, and prevent rapid β-grain growth. The intermediate cold extrusion deformation uses a medium diameter reduction deformation amount combined with medium-temperature intermediate heat treatment to induce grain recrystallization. The fine cold extrusion deformation uses a small diameter reduction deformation amount to avoid excessive deformation leading to severe work hardening, making the wire brittle, and increasing the risk of fracture. Finally, β-heat treatment is used to obtain a titanium alloy wire with an elastic modulus slightly higher than that of shape memory alloys. The extrusion molding deformation amount is significantly greater than that of traditional fixed-die drawing, enabling the wire to meet the YS / T 1077-2015 standard while improving the strength-plasticity matching and low elastic modulus of the titanium alloy wire, avoiding the risk of breakage during subsequent processing.
[0005] The present invention solves the above-mentioned technical problems through the following technical solutions.
[0006] The purpose of this invention is to provide a method for preparing β-titanium alloy wire, comprising the following steps: Hot-rolled titanium alloy coils were sequentially subjected to cold extrusion deformation, followed by heat treatment in the β single-phase region to obtain β titanium alloy wire with a diameter of Φ4.0mm ± 0.2mm. The cold extrusion deformation adopted a stepwise reduction in deformation amount, including rough cold extrusion deformation, intermediate cold extrusion deformation, and fine cold extrusion deformation. In the rough cold extrusion deformation, the deformation per pass was 15%–20%, and the total deformation was 35%–45%. In the intermediate cold extrusion deformation, the deformation per pass was 12%–17%, and the total deformation was 30%–40%. In the fine cold extrusion deformation, the deformation per pass was 7%–10%, and the total deformation was 10%–20%. After rough cold extrusion deformation, solution treatment was performed at the phase transformation point β+ (5℃–15℃), and after intermediate cold extrusion deformation, solution treatment was performed at the phase transformation point β+ (20℃–40℃).
[0007] Furthermore, the rough cold extrusion deformation includes 3 to 4 passes, with a reduction in diameter of 0.5 mm to 0.8 mm per pass; the intermediate cold extrusion deformation includes 3 to 4 passes, with a reduction in diameter of 0.35 mm to 0.5 mm per pass; and the finish cold extrusion deformation includes 1 to 2 passes, with a reduction in diameter of 0.15 mm to 0.25 mm per pass.
[0008] Furthermore, the solution treatment time was 0.5h to 1h, and the cooling method was water cooling.
[0009] Furthermore, the temperature of the β single-phase region heat treatment after precision cold extrusion deformation is the phase transformation point β+ (50℃~100℃), the heat treatment time of the β single-phase region is 0.5h~1h, and the cooling method is water cooling.
[0010] Furthermore, hot-rolled titanium alloy discs are produced by rolling titanium alloy billets in two passes to reduce the billet size to Φ8.0mm~Φ8.4mm.
[0011] Furthermore, before the first rolling, the titanium alloy billet is held at 900℃~970℃ for 2.5h~3h. After the first rolling, the titanium alloy billet is reduced to Φ100mm~Φ120mm. Before the second rolling, the titanium alloy billet is held at 800℃~900℃ for 2h~2.5h.
[0012] Furthermore, the titanium alloy billet is drawn to 200mm × L after the ingot is held at 1100℃~1150℃ for 4h~4.5h, where L is the length of the titanium alloy billet.
[0013] Furthermore, the chemical composition of β-titanium alloy wire, by mass percentage, is as follows: Al: 3.0%~4.5%; V: 20.0%~23.0%; Fe: ≤0.15%; C: ≤0.05%; N: ≤0.03%; H: ≤0.010%; O: ≤0.18%, with the balance being Ti and unavoidable impurities, totaling 100%.
[0014] Furthermore, after heat treatment in the β single-phase region, a surface peeling and deoxidation treatment is performed, with a peeling amount of 0.3 mm to 0.5 mm.
[0015] Compared with the prior art, the present invention has the following advantages: The method for preparing β-titanium alloy wire provided by this invention employs a gradient reduction in deformation amount. Large deformation combined with low-temperature heat treatment forms a coarse cold extrusion deformation, achieving rapid diameter reduction and grain refinement. A short-duration intermediate heat treatment at low temperature promotes alloy recrystallization while preventing rapid β-grain growth. The intermediate cold extrusion deformation uses a moderate diameter reduction deformation amount combined with a medium-temperature intermediate heat treatment to provide sufficient thermal activation energy for atomic diffusion and grain boundary migration, enabling grain recrystallization. Fine cold extrusion deformation uses a small diameter reduction deformation amount to avoid excessive deformation leading to severe work hardening. The β-heat treatment provides sufficient thermal activation energy for atomic diffusion and grain boundary migration, ensuring sufficient static recrystallization of the material, eliminating work hardening, and restoring the microstructure to a low-defect, high-plasticity state. The extrusion deformation amount is significantly greater than that of traditional fixed-die drawing. In summary, this invention utilizes multi-stage, gradient-based synergistic deformation and phase transformation to prepare titanium alloy wire that compensates for the lack of elasticity in pure titanium when used as eyeglass frames. Furthermore, this wire is easy to form, can be bent or shaped into complex forms, and avoids the risk of breakage during subsequent processing. This allows the wire to meet the YS / T 1077-2015 standard while improving the strength-plasticity matching and low elastic modulus of titanium alloy wire, thus avoiding the risk of breakage during subsequent processing. Attached Figure Description
[0016] Figure 1 These are microstructure images of the β-titanium alloy wires prepared in Examples 1 to 3 of this invention after solution treatment in the β single-phase region. Figure 1 In the text, a represents Example 1, b represents Example 2, and c represents Example 3. Detailed Implementation
[0017] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0018] It should be noted that the technical terms used in this invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of this invention. Unless otherwise specified, all raw materials, reagents, instruments and equipment used in the following embodiments of this invention can be purchased from the market or prepared by existing methods.
[0019] To achieve optimal wearing comfort, durability, and design freedom while ensuring sufficient strength, titanium alloy wire for eyeglasses requires a low elastic modulus. The elastic modulus of titanium alloy decreases with decreasing α-phase content, as the α-phase has a relatively high elastic modulus, typically 110 GPa to 120 GPa, while the β-phase has a lower elastic modulus, typically 70 GPa to 80 GPa. Therefore, controlling the ratio of α-phase to β-phase in the alloy can effectively control the elastic modulus. Based on this, this invention provides a method for preparing β-titanium alloy wire, which meets the YS / T 1077-2015 standard while possessing good strength-plasticity matching and a low elastic modulus, avoiding the risk of breakage during subsequent processing and forming. Specifically, it includes the following steps:
[0020] S1. After holding the TB13 ingot at 1100℃~1150℃ for 4h~4.5h, draw it to Φ200mm×L, where L is the length of the titanium alloy billet. Hold the titanium alloy billet at 900℃~970℃ for 2.5h~3h and then roll it to Φ100mm~Φ120mm. Then hold it at 800℃~900℃ for 2h~2.5h and then roll it to Φ8.0mm~Φ8.4mm to obtain a hot-rolled titanium alloy disc.
[0021] In this invention, the coarse and uneven as-cast structure of TB13 titanium alloy ingot is completely broken down and refined into a uniform and fine β-grain structure through multi-stage hot deformation by drawing and rolling, thereby obtaining a hot-rolled coil with uniform structure and stable performance, providing excellent billet for subsequent cold working.
[0022] S2. The hot-rolled titanium alloy discs are subjected to cold extrusion deformation in sequence. The cold extrusion deformation adopts a method of gradually decreasing deformation amount, including rough cold extrusion deformation, intermediate cold extrusion deformation and fine cold extrusion deformation.
[0023] In the rough cold extrusion deformation process, the deformation per pass is 15%–20%, and the total deformation is 35%–45%. In some embodiments, the rough cold extrusion deformation includes 3 to 4 passes, with a reduction in diameter of 0.5 mm to 0.8 mm per pass. After rough cold extrusion deformation, solution treatment is performed at the phase transformation point β+ (5℃–15℃) for 0.5 h to 1 h, and water cooling is used.
[0024] It should be noted that during the large deformation cold extrusion process, the deformation energy accumulated inside the wire mainly comes from the proliferation of dislocation entanglement, cellular substructure, and high-density point defects. The intense plastic flow under large deformation causes a sharp increase in intragranular distortion energy, and the recrystallization driving force is significantly higher than under small deformation conditions. This high driving force significantly reduces the critical nucleation work for recrystallization, allowing recrystallization to be completed at a relatively low temperature. This invention uses large deformation combined with low-temperature heat treatment to form rough cold extrusion deformation, achieving rapid diameter reduction and grain refinement. The short-time intermediate heat treatment at low temperature promotes recrystallization of the alloy while avoiding rapid growth of β grains.
[0025] During the intermediate cold extrusion deformation process, the deformation per pass is 12%–17%, and the total deformation is 30%–40%. In some embodiments, the intermediate cold extrusion deformation includes 3–4 passes, with a reduction in diameter of 0.35 mm–0.5 mm per pass. After intermediate cold extrusion deformation, solution treatment is performed at the phase transformation point β+ (20℃–40℃) for 0.5 h–1 h, and water cooling is used.
[0026] It should be noted that intermediate cold extrusion deformation employs a moderate diameter reduction deformation combined with a medium-temperature intermediate heat treatment. This is because the reduced diameter reduction weakens dislocation multiplication and entanglement, resulting in a relative decrease in deformation storage energy. At this point, the temperature must be increased to compensate for the insufficient driving force, providing sufficient thermal activation energy for atomic diffusion and grain boundary migration; otherwise, recrystallization will not proceed sufficiently due to insufficient driving force. If a low temperature is used, the driving force provided by the moderate deformation is insufficient, resulting in a low recrystallization nucleation rate of β grains, potentially leading to a mixed-grain structure with "partial recrystallization" and deteriorating performance.
[0027] In the process of rough cold extrusion deformation and intermediate cold extrusion deformation, the alloy retains only a single β phase grain during single-phase region solution treatment. The crystal structure of the β phase is BCC structure, which has more slip systems than the α phase, making it easier to deform and exhibiting excellent plasticity, which is beneficial for subsequent cold working.
[0028] During the precision cold extrusion deformation process, the deformation per pass is 7%–10%, and the total deformation is 8%–20%. In some embodiments, the precision cold extrusion deformation includes 1 to 2 passes, with a reduction in diameter of 0.15 mm to 0.25 mm per pass. It should be noted that precision cold extrusion deformation, with its small reduction in diameter, better controls dimensional accuracy and surface finish. Excessive deformation can lead to severe work hardening, making the wire brittle and increasing the risk of breakage.
[0029] After heat treatment in the S3 and β single-phase regions, β-titanium alloy wire was obtained. The β single-phase region heat treatment temperature was β+ (50℃~100℃), and the heat treatment time was 0.5h~1h, with water cooling as the cooling method. This is because the small deformation amount provided by precision cold extrusion deformation provides relatively limited stored energy. The high-temperature environment provides sufficient thermal activation energy for atomic diffusion and grain boundary migration, ensuring sufficient static recrystallization of the material. This process resets the dislocation structure, eliminates work hardening, and restores the microstructure to a low-defect, high-plasticity state, thereby obtaining excellent comprehensive mechanical properties.
[0030] The phase transition point β is 730℃.
[0031] This invention employs a single-phase gradient heat treatment with β-phase heat treatment to control the size distribution of the β-phase. The single-phase region is chosen for the heat treatment due to the difference in crystal structure between the α and β phases. The α phase has an HCP structure with fewer slip systems, making it less prone to deformation and thus providing a strengthening effect. This yields titanium alloy wire with slightly higher elasticity than shape memory alloys. The extrusion deformation is significantly greater than that of traditional fixed-die drawing. This allows the wire to meet the YS / T 1077-2015 standard while improving the strength-plasticity balance and low elastic modulus of the titanium alloy wire, avoiding the risk of breakage during subsequent processing.
[0032] In some embodiments, the TB13 titanium alloy wire provided by the present invention has the following chemical composition by mass percentage: Al (aluminum): 3.0%–4.5%; V (vanadium): 20.0%–23.0%; Fe (iron): ≤0.15%; C (carbon): ≤0.05%; N (nitrogen): ≤0.03%; H (hydrogen): ≤0.010%; O (oxygen): ≤0.18%, with the balance being Ti (titanium) and unavoidable impurities, totaling 100%.
[0033] After heat treatment in the S4 and β single-phase regions, a surface peeling and deoxidation process is performed, with a peeling amount of 0.3mm to 0.5mm, to obtain β titanium alloy wire with a diameter of Φ4.0mm ± 0.2mm.
[0034] In summary, this invention proposes a method for preparing β-titanium alloy wire. This method involves cold extrusion molding to produce β-titanium alloy wire using a gradually decreasing deformation rate. Through multiple passes of synergistic deformation and phase transformation, the rough cold extrusion deformation, with its large deformation amount combined with low-temperature heat treatment, and solution treatment at β+ (5℃~15℃) above the phase transformation point, achieves rapid diameter reduction, refines grains, and prevents rapid β grain growth. The fine cold extrusion deformation, with its small diameter reduction deformation, avoids excessive deformation that could lead to severe work hardening, making the wire brittle and increasing the risk of fracture. Finally, β heat treatment yields a titanium alloy wire with an elastic modulus slightly higher than that of shape memory alloys. Furthermore, compared to the 100~110 GPa elastic modulus of pure titanium, the titanium alloy wire prepared by this invention compensates for the insufficient elasticity of pure titanium when used as eyeglass frames. This wire is also easy to form, can be bent or formed into complex shapes, and avoids the risk of breakage during subsequent processing. This method involves extrusion molding of titanium alloy wire rods through three stages: rough extrusion, intermediate extrusion, and fine extrusion. The extrusion molding deformation is significantly greater than that of traditional fixed die drawing, which improves the problems of long preparation cycle and poor surface precision caused by surface pickling of finished products in traditional titanium alloy wire. This method enables the wire to meet the YS / T 1077-2015 standard while having good strength-plasticity matching and low elastic modulus, avoiding the risk of cracking during subsequent processing.
[0035] The following specific examples will provide further explanation.
[0036] Example 1 A method for preparing β-titanium alloy wire includes the following steps: S1. The alloy is proportioned according to the following chemical elements: Al: 3.99%; V: 21.62~21.83%; Fe: 0.083%~0.091%; C: 0.012%~0.014%; N: 0.007%~0.006%; H: 0.0006%; O: 0.108%~0.110%, with the balance being Ti and unavoidable impurities, totaling 100%. After the materials are proportioned, they are mixed, electrode blocks are pressed, consumable electrodes are welded, and then the mixture is smelted three times in a VAR process to form an ingot.
[0037] S2. Forging and rolling: After holding the ingot at 1100℃ for 4 hours, it is drawn to 200mm×L to obtain a square billet; then, after holding at 950℃ for 3 hours, it is rolled to Φ100mm in the first heat, and after holding at 880℃ for 2 hours, it is rolled to Φ8.2mm±0.2mm in the second heat.
[0038] S3. Cold Extrusion Forming: Hot-rolled titanium alloy wire rods are extruded into wire blanks in three stages: rough extrusion, intermediate extrusion, and finish extrusion. The rough extrusion includes three passes, with single-pass diameter reductions of 0.7mm, 0.6mm, and 0.6mm, and single-pass extrusion deformations of 16.73%, 15.76%, and 17.11%, respectively, for a total deformation of 41.86%. The intermediate extrusion includes three passes, with single-pass diameter reductions of 0.45mm, 0.4mm, and 0.35mm, and single-pass extrusion deformations of 14.21%, 13.66%, and 12.89%, respectively, for a total deformation of 35.47%. The finish extrusion includes two passes, with single-pass diameter reductions of 0.2mm and 0.2mm, and single-pass extrusion deformations of 8.0% and 8.33%, respectively, for a total deformation of 15.66%.
[0039] In the process of rough extrusion, the billet is kept at 735℃ for 40 minutes and then cooled to room temperature by water. In the intermediate extrusion process, the billet is kept at 770℃ for 40 minutes and then cooled by water.
[0040] S4. The cold-extruded titanium alloy wire is held at 780℃ for 60 minutes for β single-phase heat treatment, and then water-cooled to room temperature to obtain wire blank. The wire blank is then subjected to surface deoxidation treatment to remove the surface oxide scale. The peeling amount is 0.5mm, resulting in titanium alloy wire with a size of Φ4.0mm±0.2mm.
[0041] Example 2 A method for preparing β-titanium alloy wire includes the following steps: S1. The alloy is proportioned according to the following chemical elements: Al: 3.94%~4.05%; V: 20.98%~21.39%; Fe: 0.071%~0.082%; C: 0.010%; N: 0.007%~0.009%; H: 0.0006%; O: 0.103%~0.116%, with the balance being Ti and unavoidable impurities, totaling 100%. After the materials are proportioned, they are mixed, electrode blocks are pressed, consumable electrodes are welded, and then the mixture is smelted three times in a VAR process to form an ingot.
[0042] S2. Forging and rolling: After holding the ingot at 1150℃ for 4 hours, it is drawn to ○200mm×L to obtain a square billet; then, after holding at 920℃ for 2.5 hours, it is rolled to Φ120mm in the first heat, and after holding at 850℃ for 2 hours, it is rolled to Φ8.2mm±0.2mm in the second heat.
[0043] S3. Cold Extrusion Forming: Hot-rolled titanium alloy wire rods are extruded into wire blanks in three stages: rough extrusion, intermediate extrusion, and finish extrusion. The rough extrusion includes three passes, with single-pass diameter reductions of 0.8mm, 0.7mm, and 0.6mm, and single-pass extrusion deformations of 18.34%, 17.80%, and 16.87%, respectively, for a total deformation of 44.20%. The intermediate extrusion includes three passes, with single-pass diameter reductions of 0.5mm, 0.5mm, and 0.4mm, and single-pass extrusion deformations of 15.48%, 16.77%, and 14.79%, respectively, for a total deformation of 35.47%. The finish extrusion includes two passes, with single-pass diameter reductions of 0.2mm and 0.2mm, and single-pass extrusion deformations of 8.16% and 8.51%, respectively, for a total deformation of 15.91%.
[0044] In the process of rough extrusion, the billet is kept at 735℃ for 40 minutes and then cooled to room temperature by water. In the intermediate extrusion process, the billet is kept at 750℃ for 40 minutes and then cooled by water.
[0045] S4. The cold-extruded titanium alloy wire is held at 800℃ for 60 minutes for β single-phase heat treatment, and then water-cooled to room temperature to obtain wire blank. The wire blank is then subjected to surface deoxidation treatment to remove the surface oxide scale. The peeling amount is 0.5mm, resulting in titanium alloy wire with a size of 4.0mm±0.2mm.
[0046] Example 3 A method for preparing β-titanium alloy wire includes the following steps: S1. The alloy is proportioned according to the following chemical elements: Al: 3.75%–3.9%; V: 22.12%–22.34%; Fe: 0.062%–0.065%; C: 0.015%–0.018%; N: 0.009%–0.010%; H: 0.0010%–0.0018%; O: 0.112%–0.117%, with the balance being Ti and unavoidable impurities, totaling 100%. After the materials are proportioned, they are mixed, electrode blocks are pressed, consumable electrodes are welded, and then the alloy is smelted three times in a VAR process to form an ingot.
[0047] S2. Forging and rolling: After holding the ingot at 1100℃ for 4.5h, it is drawn to ○200mm×L to obtain a square billet; then, after holding at 930℃ for 3h, it is rolled to Φ100mm in the first heat, and after holding at 830℃ for 2h, it is rolled to Φ8.2mm±0.2mm in the second heat.
[0048] S3. Cold Extrusion Forming: Hot-rolled titanium alloy wire rods are extruded into wire blanks in three stages: rough extrusion, intermediate extrusion, and finish extrusion. The rough extrusion includes three passes, with single-pass diameter reductions of 0.8 mm, 0.65 mm, and 0.55 mm, and single-pass deformations of 19%, 17.24%, and 1610%, respectively, for a total deformation of 43.75%. The intermediate extrusion includes three passes, with single-pass diameter reductions of 0.5 mm, 0.45 mm, and 0.4 mm, and single-pass deformations of 15.97%, 15.69%, and 15.21%, respectively, for a total deformation of 39.94%. The finish extrusion includes two passes, with single-pass diameter reductions of 0.2 mm and 0.15 mm, and single-pass deformations of 8.42% and 6.63%, respectively, for a total deformation of 14.49%.
[0049] In the process of rough extrusion, the billet is kept at 740℃ for 50 minutes and then cooled to room temperature by water. In the intermediate extrusion process, the billet is kept at 755℃ for 50 minutes and cooled by water.
[0050] S4. The cold-extruded titanium alloy wire is held at 820℃ for 60 minutes for β single-phase heat treatment, and then water-cooled to room temperature to obtain wire blank. The wire blank is then subjected to surface deoxidation treatment to remove the surface oxide scale. The peeling amount is 0.5mm, resulting in titanium alloy wire with a size of Φ4.0mm±0.2mm.
[0051] Comparative Example 1 The preparation method of TB13 titanium alloy wire includes the following steps: S1. The alloy is proportioned according to the following chemical elements: Al: 3.99%; V: 21.62~21.83%; Fe: 0.083%~0.091%; C: 0.012%~0.014%; N: 0.007%~0.006%; H: 0.0006%; O: 0.108%~0.110%, with the balance being Ti and unavoidable impurities, totaling 100%. After the materials are proportioned, they are mixed, electrode blocks are pressed, consumable electrodes are welded, and then the mixture is smelted three times in a VAR process to form an ingot.
[0052] S2. Forging and rolling: After holding the ingot at 1100℃ for 4 hours, it is drawn to 200mm×L to obtain a square billet; then, after holding at 950℃ for 3 hours, it is rolled to Φ100mm in the first heat, and after holding at 880℃ for 2 hours, it is rolled to Φ8.0mm~Φ8.4mm in the second heat.
[0053] S3. Cold Extrusion Forming: Hot-rolled titanium alloy wire rods are cold-extruded in three consecutive three-pass cycles. The three consecutive three-pass cold extrusions are performed to diameters of ϕ7.0mm~7.5mm, ϕ6.0mm~6.4mm, and ϕ4.4mm~4.5mm, respectively. After each multi-pass cold extrusion, the wire is subjected to an intermediate heat treatment at 750℃ for 1 hour, followed by air cooling to room temperature to obtain a wire blank. The wire is then subjected to surface peeling to obtain TB13 titanium alloy wire with a size of Φ4.0mm±0.2mm.
[0054] The performance of the β-titanium alloy wires prepared in the above examples and comparative examples was tested, and the results are shown in Table 1. The mechanical properties of the wires obtained through the processes in Examples 1, 2, 3, and Comparative Example 1 show that the wires obtained through the processes in the examples all meet the standard requirements, exhibiting good comprehensive mechanical properties and an elastic modulus controlled below 80 GPa. However, the mechanical properties of the titanium alloy wire prepared through the process in Comparative Example 1 do not meet the standard requirements.
[0055] Table 1 Mechanical properties of β-titanium alloy wire Example 1 722.15 711.35 20.33 74.30 77 Example 2 717.35 705.16 23.73 71.27 78.74 Example 3 715.53 697.33 28.25 72.38 79.43 Comparative Example 675 611 17.5 73 / Standard requirements ≥700 ≥650 ≥15 ≥55 / Figure 1 These are microstructure images of the β-titanium alloy wires prepared in Examples 1 to 3 of this invention after solution treatment in the β single-phase region. Figure 1 In the text, a represents Example 1, b represents Example 2, and c represents Example 3. Figure 1 As shown, the microstructure after solution treatment in the single-phase region consists of single equiaxed β-phase grains.
[0056] It should be noted that when numerical ranges are involved in this invention, it should be understood that both endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as in the embodiments, preferred embodiments are described here to avoid redundancy. Although preferred embodiments of the invention have been described, those skilled in the art, once they understand the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of this invention.
[0057] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.
Claims
1. A method for preparing β-titanium alloy wire, characterized in that, Includes the following steps: Hot-rolled titanium alloy discs were sequentially subjected to cold extrusion deformation, followed by β single-phase heat treatment to obtain β titanium alloy wire with a diameter of Φ4.0mm ± 0.2mm. The cold extrusion deformation process employs a progressively decreasing deformation method, including rough cold extrusion deformation, intermediate cold extrusion deformation, and fine cold extrusion deformation. During rough cold extrusion deformation, the deformation per pass is 15%–20%, and the total deformation is 35%–45%. During intermediate cold extrusion deformation, the deformation per pass is 12%–17%, and the total deformation is 30%–40%. During fine cold extrusion deformation, the deformation per pass is 7%–10%, and the total deformation is 10%–20%. After rough cold extrusion deformation, solution treatment is performed at the phase transformation point β+ (5℃–15℃), and after intermediate cold extrusion deformation, solution treatment is performed at the phase transformation point β+ (20℃–40℃).
2. The method for preparing β-titanium alloy wire according to claim 1, characterized in that, The rough cold extrusion deformation includes 3 to 4 passes, with a reduction in diameter of 0.5 mm to 0.8 mm per pass; the intermediate cold extrusion deformation includes 3 to 4 passes, with a reduction in diameter of 0.35 mm to 0.5 mm per pass; and the finish cold extrusion deformation includes 1 to 2 passes, with a reduction in diameter of 0.15 mm to 0.25 mm per pass.
3. The method for preparing β-titanium alloy wire according to claim 1, characterized in that, The solution treatment time was 0.5h to 1h, and the cooling method was water cooling.
4. The method for preparing β-titanium alloy wire according to claim 1, characterized in that, The temperature for heat treatment of the β single-phase region after cold extrusion is the phase transformation point β+ (50℃~100℃), the heat treatment time of the β single-phase region is 0.5h~1h, and the cooling method is water cooling.
5. The method for preparing β-titanium alloy wire according to claim 1, characterized in that, Hot-rolled titanium alloy discs are produced by rolling titanium alloy billets in two passes to reduce the billet diameter to Φ8.0mm~Φ8.4mm.
6. The method for preparing β-titanium alloy wire according to claim 5, characterized in that, Before the first rolling, the titanium alloy billet is held at 900℃~970℃ for 2.5h~3h. After the first rolling, the titanium alloy billet is reduced to Φ100mm~Φ120mm. Before the second rolling, the titanium alloy billet is held at 800℃~900℃ for 2h~2.5h.
7. The method for preparing β-titanium alloy wire according to claim 5, characterized in that, The titanium alloy billet is drawn to a length of 200mm × L after the ingot is held at 1100℃~1150℃ for 4h~4.5h, where L is the length of the titanium alloy billet.
8. The method for preparing β-titanium alloy wire according to claim 1, characterized in that, The chemical composition of β-titanium alloy wire, by mass percentage, is: Al: 3.0%–4.5%; V: 20.0%~23.0%; Fe: ≤0.15%; C: ≤0.05%; N: ≤0.03%; H: ≤0.010%; O: ≤0.18%, with the balance being Ti and unavoidable impurities, totaling 100%.
9. The method for preparing β-titanium alloy wire according to claim 1, characterized in that, After heat treatment in the β single-phase region, surface peeling and deoxidation treatment is performed, with a peeling amount of 0.3 mm to 0.5 mm.
Citation Information
Patent Citations
Preparation method for improving mechanical property of TB13 titanium alloy wire for spectacle frame
CN116532510A
Titanium alloy wire drawing preparation method and titanium alloy wire
CN122099098A
